The nutritional adequacy of vegetarian menu substitutions in urban Kansas childcare centers - Jindrich, Caitlin (My University, 2021)
I completed my Applied Practice Experience (APE) at Fort Riley’s Department of Public Health (DPH); whose mission, “is to promote health and wellness, and to prevent disease and injury of Soldiers and military retirees, their families, and Army Civilian employees at Fort Riley through workplace and community health.” Fort Riley was the first military installation to earn Public Health Accreditation Board (PHAB) accreditation. During the course of my APE, I created the first Annual Report for DPH, three months’ worth of bulletin board content and recipes for the Riley County and Irwin Army Community Hospital (IACH) Women, Infants, and Children (WIC) offices, wrote an article on COVID-19 for the purpose of being published in Fort Riley’s newspaper and to be sent as a secure message to Fort Riley healthcare beneficiaries, and a decision flowchart for medical clinics throughout IACH’s system on where/how to treat persons under investigation (PUI).
Keywords: Fort Riley Kansas; Public Health Accreditation Board